Value of Chest X-ray Combined with Perfusion Scan versus Ventilation/Perfusion Scan in Acute Pulmonary Embolism - de Groot, Marco R.; Turkstra, Franktien; van Marwijk Kooy, Marinus; Oostdijk, Ad H. J.; van Beek, Edwin J. R.; Büller, Harry R. (Thrombosis and Haemostasis, 2000)
BackgroundThe main purpose of ventilation scanning, as adjunct to perfusion lung scintigraphy, in acute pulmonary embolism is to allow for the classification of segmental perfusion defects as mismatched, which is generally accepted as proof for the presence of pulmonary embolism. We examined whether this function of the ventilation scan could be replaced by the chest X-ray.MethodsIn 389 consecutive patients with suspected pulmonary embolism and at least one segmental perfusion defect we classified the ventilation/perfusion (V/Q) scan and chest X-ray/perfusion (X/Q) scan as either mismatched or matched. Furthermore we analyzed whether this comparison was different in subgroups of patients with concomitant congestive heart failure or chronic obstructive pulmonary disease.Results Overall agreement between the X/Q and V/Q scan diagnostic category was found in 341 of 389 patients (88%; 95% CI 84-92%). The positive predictive value for obtaining a mismatched V/Q scan result in case of a mismatched X/Q scan result was 86% (95% CI 81-90%). If the X/Q scan yielded only matched defects the V/Q scan resulted in the same classification in 90% (95% CI 85-95%). Analysis of the small subgroup of patients with chronic obstructive pulmonary disease showed that a mismatched X/Q scan was confirmed by V/Q scanning in 21 of 34 cases (62%; 95% CI 45-78%).ConclusionThis study shows that in the great majority of patients with clinically suspected acute pulmonary embolism combination of chest X-ray with perfusion scintigraphy reliably replaced ventilation/perfusion scintigraphy in defining (mis)-matching of segmental perfusion defects. These results need confirmation before the chest X-ray can fully obviate the use of ventilation scintigraphy.
Keywords: Chest X-ray; ventilation/perfusion scan; pulmonary embolism